The Inheritance Pattern of Wayang Orang Art in Padhepokan Tjipta Boedajatutup Ngisor Lereng Merapi - Suparti, Suparti; Triyanto, Triyanto; Cahyono, Agus (Universitas Negeri Semarang, 2017)
The purpose of the research is to, the inheritance pattern of Tjipta Boedaya’s Wayang Orang. The method of the research was qualitative method by using the approach of interdicipline which utilized etnochoreology study, anthropology, and sociology. The inheritance pattern of Tjipta Boedaya’s Wayang Orang. The location of the reasearch was at Padhepokan Tjipta Boedaya, dusun tutup ngisor. The technique of the data collection was using observations, interviews, and study dokumen, the technique of data validation was using triangulation, member check, and making thick description. The technique of the theory data analysis was using the concept which has been arraanged before and throughed four analysis stages which were data collection, reduction, presentation, and verification. The result of the research inheritance pattern of Wayang Orang divided into two paths, they were family path and environment path. Inheritance which been inherited including stories, themes, movements, cosmetics,and accompaniment. Inheritance pattern through family and environtment became the key of the establishment of Tjipta Boedaya’ Wayang Orang.